Hospital and Surgeon Selection for Medicare Beneficiaries With Stage II/III Rectal Cancer: The Role of Rurality, Distance to Care, and Colonoscopy Provider. Issue 4 (October 2021) - Chioreso, Catherine; Gao, Xiang; Gribovskaja-Rupp, Irena; Lin, Chi; Ward, Marcia M.; Schroeder, Mary C.; Lynch, Charles F.; Chrischilles, Elizabeth A.; Charlton, Mary E.
Abstract : Objective: To determine factors associated with rectal cancer surgery performed at high-volume hospitals (HVHs) and by high-volume surgeons (HVSs), including the roles of rurality and diagnostic colonoscopy provider characteristics. Summary of Background Data: Although higher-volume hospitals/surgeons often achieve superior surgical outcomes, many rectal cancer resections are performed by lower-volume hospitals/surgeons, especially among rural populations. Methods: Patients age 66+ diagnosed from 2007 to 2011 with stage II/III primary rectal adenocarcinoma were selected from surveillance, epidemiology, and end results-medicare data. Patient ZIP codes were used to classify rural status. Hierarchical logistic regression was used to determine factors associated with surgery by HVH and HVS. Results: Of 1601 patients, 22% were rural and 78% were urban. Fewer rural patients received surgery at a HVH compared to urban patients (44% vs 65%; P < 0.0001). Compared to urban patients, rural patients more often had colonoscopies performed by general surgeons (and less often from gastroenterologists or colorectal surgeons), and lived substantially further from HVHs; these factors were both associated with lower odds of surgery at a HVH or by a HVS. In addition, whereas over half of both rural and urban patients received their colonoscopy and surgery at the same hospital, rural patients who stayed at the same hospital were significantly less likely to receive surgery at a HVH or by a HVS compared to urban patients. Conclusions: Rural rectal cancer patients are less likely to receive surgery from a HVH/HVS. The role of the colonoscopy provider has important implications for referral patterns and initiatives seeking to increase centralization.